2013
DOI: 10.1209/0295-5075/102/50008
|View full text |Cite
|
Sign up to set email alerts
|

The intermediate level statistics in dynamically localized chaotic eigenstates

Abstract: We demonstrate that the energy or quasienergy level spacing distribution in dynamically localized chaotic eigenstates is excellently described by the Brody distribution, displaying the fractional power law level repulsion. This we show in two paradigmatic systems, namely for the fully chaotic eigenstates of the kicked rotator at K = 7, and for the chaotic eigenstates in the mixed-type billiard system (Robnik 1983), after separating the regular and chaotic eigenstates by means of the Poincaré Husimi function, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
6
30
0
Order By: Relevance
“…His result showed that the parameter β, which was obtained using the Izrailev distribution, is functionally related to the localization measure defined as the information entropy of the eigenstates in the angular momentum representation. His results were recently confirmed and extended, with the much greater numerical accuracy and statistical significance [38,39].…”
Section: Introductionmentioning
confidence: 76%
“…His result showed that the parameter β, which was obtained using the Izrailev distribution, is functionally related to the localization measure defined as the information entropy of the eigenstates in the angular momentum representation. His results were recently confirmed and extended, with the much greater numerical accuracy and statistical significance [38,39].…”
Section: Introductionmentioning
confidence: 76%
“…The main motivation for the present work was our recent research on the quantum kicked rotator [24,25], which is the quantized classical kicked rotator, described by the standard map. For the systematic understanding of the quantum kicked rotator and its semiclassical theory, a complete survey of the standard map is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we study the diffusion properties in area preserving maps, exemplified by the standard map of Chirikov. This work is actually motivated by our extensive study [24,25] of the quantum kicked rotator introduced by Casati et al [26], in which -at the semiclassical level -it is necessary to understand in detail the classical diffusion, in order to set up a theory of (exponential) quantum (or dynamical) localization. Our previous work was stimulated by the series of pioneering and classic papers by Izrailev [27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the problem of calculating the distribution of the localization length (or its inverse) in the semiclassical framework is open for the future work. Also, the derivation of the Brody distribution to explain the level spacing distribution of the energies [29,31,32] in time-independent systems, and of the quasienergies [30,38,39] in time-periodic systems, of chaotic eigenstates, is still open for the future.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant papers dealing with the mixed type regime after the work [19] are [21][22][23][24][25][26][27][28] and the most recent advance was published in [29][30][31][32]. If the couplings between the regular eigenstates and chaotic eigenstates become important, due to the dynamical tunneling, we can use the ensembles of random matrices that capture these effects [33].…”
Section: Introductionmentioning
confidence: 99%